1983
DOI: 10.1073/pnas.80.23.7104
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the Epstein-Barr virus nuclear antigen and to rheumatoid arthritis nuclear antigen identify the same polypeptide.

Abstract: Patients with seropositive rheumatoid arthritis (RA) have elevated titers of precipitating antibody toward an antigen designated RA nuclear antigen (RANA). Anti-RANA reactivity has been associated with prior Epstein-Barr virus (EBV) be reactive when a complement fixation assay was used in the immunoblot. Finally, when the Mr 80,000 antigen was used to absorb an anti-RANA/anti-EBNA serum, both antibodies were reduced.The rheumatoid arthritis nuclear antigen (RANA) was first identified in WI-L2 cells by a prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…We found that inclusion of SDS in the transfer buffer was required to obtain efficient transfer of EBNA-2 onto nitrocellulose, and that the binding of EBNA-2 to the nitrocellulose was not stable since overnight incubation of the nitrocellulose in saline resulted in the loss of a significant amount of the antigen. Billings et a1 (10) did not include SDS in their transfer buffer, and this is the likely reason for the discrepancy between results.…”
Section: Discussionmentioning
confidence: 74%
“…We found that inclusion of SDS in the transfer buffer was required to obtain efficient transfer of EBNA-2 onto nitrocellulose, and that the binding of EBNA-2 to the nitrocellulose was not stable since overnight incubation of the nitrocellulose in saline resulted in the loss of a significant amount of the antigen. Billings et a1 (10) did not include SDS in their transfer buffer, and this is the likely reason for the discrepancy between results.…”
Section: Discussionmentioning
confidence: 74%
“…EBV infection is widespread, and 95% of all adults display serologic signs of a previous infection. It is known that patients with RA have elevated levels of antibodies to latent and replicative EBV proteins (36) and in particular to EBNA-1 (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Among several viruses that have been implicated in the pathogenesis of RA (6)(7)(8), a possible relationship between Epstein-Barr virus (EBV) and RA was initially suspected from disease-specific, altered humoral immune responses toward different viral antigens, such as the Epstein-Barr nuclear antigens (EBNAs) 1 and 2, in patients with RA (9)(10)(11)(12). Antibodies against a glycine-alanine repeat in the EBNA-1 molecule were shown to cross-react with a 62-kd protein present in the synovial tissues of patients with RA but absent from the joints of patients with osteoarthritis (OA) and from normal subjects (13).…”
mentioning
confidence: 99%